1983
DOI: 10.1083/jcb.96.5.1227
|View full text |Cite
|
Sign up to set email alerts
|

Specialization of the macrophage plasma membrane at sites of interaction with opsonized erythrocytes.

Abstract: We incubated mouse peritoneal macrophages for 3-8 min at 37°C with antibodycoated sheep erythrocytes and examined regions of close interaction between the two cell types by electron microscopy. At sites of focal macrophage-erythrocyte contact we observed a distinctive specialization of the macrophage plasma membrane consisting of a prominent subplasmalemmal band of electron-dense material, ~25-35 nm in thickness. In many instances, this band showed a periodic substructure similar to that seen in clathrin coats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Several electron microscopy studies on macrophages have reported the enrichment of nascent phagosomal membranes with large flat clathrin patches, which disappear after 30 min (Aggeler and Werb, 1982;Montesano et al, 1983;Clerc and Sansonetti, 1989). Clathrin-coated pits have been also observed on phagosomes upon engagement of Fc receptors in phagocytic RBL-2H3 cells (Castellano et al, 2000).…”
Section: Ap-1 Is Required For Efficient Phagocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…Several electron microscopy studies on macrophages have reported the enrichment of nascent phagosomal membranes with large flat clathrin patches, which disappear after 30 min (Aggeler and Werb, 1982;Montesano et al, 1983;Clerc and Sansonetti, 1989). Clathrin-coated pits have been also observed on phagosomes upon engagement of Fc receptors in phagocytic RBL-2H3 cells (Castellano et al, 2000).…”
Section: Ap-1 Is Required For Efficient Phagocytosismentioning
confidence: 99%
“…The presence of clathrin on membranes of forming phagosomes (Aggeler and Werb, 1982;Montesano et al, 1983;Clerc and Sansonetti, 1989;Castellano et al, 2000;Tse et al, 2003) suggested that clathrin-associated adaptor complexes could associate with phagosomes. To test this hypothesis, mouse peritoneal macrophages were incubated with zymosan particles and stained with anti-␥-adaptin (AP-1) or anti-␣-adaptin (AP-2).…”
Section: 〈P-1 Localizes To Nascent Phagosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep erythrocytes (SRBCs) (BioMerieux, Charbonnier les Bains, France) were opsonized with a rabbit antiserum (20). Resealed ghosts were prepared as described (21) tTo whom reprint requests should be addressed.…”
Section: Methodsmentioning
confidence: 99%
“…The total exudate population (TEP) consisting mostly of macrophages (26) was lysed directly by Nonidet P-40 for isolation of nuclei as previously described (11) or cultured in petri dishes with supplemented Dulbecco modified Eagle medium for 18 h. The adherent macrophage population, resting or stimulated, was washed with phosphate-buffered saline (PBS), detached with a rubber policeman in Hanks medium containing powdered nonfat milk (5 mg/ml) and 1 mM dithiothreitol and supplemented with a cocktail of protease inhibitors (50 ,ug each of pepstatin A, leupeptin, chymostatin, and antipain per ml, 0.5 mM phenylmethylsulfonyl fluoride, 200 kallikrein inactivator units of aprotinin per ml, 78 ,ug of benzamidine per ml), and centrifuged for 10 min at 300 x g and 4°C; the cell pellet was lysed with Nonidet P-40 for isolation of nuclei. To prevent adherence, the TEP was incubated in Teflon beakers for 18 h and washed three times with PBS by centrifugation at 300 x g and 4°C, and the cell pellet was lysed by Nonidet P-40. Sheep erythrocytes (Behring AG, Marburg, Germany) were opsonized with a heat-inactivated (30 min at 56°C) rabbit antiserum (30), and 1 ml (50% packed cell volume) was added to 10 ml of medium per 100-mm petri dish. Cycloheximide (Sigma), cholera toxin (Sigma), N6,02-dibu-tyryladenosine-3',5'-cyclic monophosphate (dbcAMP) (Sigma), and 3-isobutyl-1-methylxanthine (IBMX) (Sigma) were added to the cultures at the concentrations indicated in the figure legends.…”
Section: Methodsmentioning
confidence: 99%